Capture Fishery Production in Bintan Regency - Faisal, La Ode M; Nevrita, Nevrita; Apdilah, Dony (Faculty of Fisheries and Marine, Universitas Riau, 2021)
The waters of Bintan Island are included in the deep sea waters of the South China Sea, within the Indonesian Exclusive Economic Zone, the potential for fish resources in the territorial waters and the South China Sea reaches 378.2 tons, with the allowable catch of 302.5 thousand tons. From this potential, the potential for fish resources that enter the territorial waters of Bintan Regency is 106,018 tons with a allowable catch of 50,287 tons. The purpose of the preparation of this scientific article is to provide information about capture fisheries production in Bintan Regency. The preparation of this scientific article was carried out in April 2021 in Bintan Regency using a descriptive analysis based on a literature review using secondary data as a source of information. The volume of fishery production originating from fishing efforts in Bintan Regency was recorded at 53,338.45 tons in 2017, while in 2018 and 2019 it was 54,682.27 tons and 55,604.40 tons, respectively. The amount of capture fisheries production in Bintan Regency has increased over the last 3 years (2017 - 2019).